2001
DOI: 10.1103/revmodphys.73.119
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of chiral symmetry and the lattice

Abstract: I explore the non-perturbative issues entwining lattice gauge theory, anomalies, and chiral symmetry. After briefly reviewing the importance of chiral symmetry in particle physics, I discuss how anomalies complicate lattice formulations.Considerable information can be deduced from effective chiral Lagrangians, helping interpret the expectations for lattice models and elucidating the role of the CP violating parameter Θ. I then turn to a particularly elegant scheme for exploring this physics on the lattice. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 116 publications
0
118
0
Order By: Relevance
“…Consequently it does not have spontaneous chiral symmetry breaking and hence no (pseudo-) Goldstone bosons and no easy definition of the quark mass [3]. In the lattice regularisation it is, however, possible to enhance the symmetry artificially by adding extra valence quarks which are quenched, that is, are not taken into account in the Boltzmann-weight of the gauge configurations by their fermion determinants.…”
Section: Partially Quenched Viewpointmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently it does not have spontaneous chiral symmetry breaking and hence no (pseudo-) Goldstone bosons and no easy definition of the quark mass [3]. In the lattice regularisation it is, however, possible to enhance the symmetry artificially by adding extra valence quarks which are quenched, that is, are not taken into account in the Boltzmann-weight of the gauge configurations by their fermion determinants.…”
Section: Partially Quenched Viewpointmentioning
confidence: 99%
“…A dramatic consequence of the absence of (broken) chiral symmetry is the difficulty to find a unique definition of the point with zero quark mass in parameter space [3]. (For an excellent summary and discussion of this problem see [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews discussing chiral symmetry on the lattice are found in Refs. [134,153,305,432,433,558].…”
Section: Fermions On the Latticementioning
confidence: 99%
“…The lattice provides the primary non-perturbative method in field theory, but issues related to anomaly cancellation make that approach rather complicated. [21] Effective chiral Lagrangians provide another powerful route to non-perturbative information, although in a less quantitative manner due to increasing numbers of arbitrary parameters at higher order. To understand these issues better, the solvable models in two dimensions can provide insight into how chiral symmetry works.…”
Section: Four Dimensional Motivationsmentioning
confidence: 99%